DUKU (Lansium domesticum) STEM BARK GEL PROMOTES HEALING OF ORAL ULCERS IN WISTAR RATS: AN IN VIVO STUDY - Siti Rusdiana Puspa Dewi; Pudji Handayani; Jessi Miranda; Shanty Chairani; Rahmatullah Irfani (Jurnal Kesehatan Gigi dan Mulut (JKGM), 2026)
Background: Oral ulcers are common and usually managed with topical medications; however, prolonged use of these medications may lead to various side effects. Duku (Lansium domesticum) stem bark contains flavonoids, saponins, alkaloids, and Triterpenes that may promote healing. This study investigated the impact of duku stem bark extract gel on the healing of oral ulcers in Wistar rats. Methods: An experimental study was done with 25 wistar strain rats and were divided into 5 tested groups, namely negative control, positive control (0,1% triamcinolone acetonide), and the experimental group with three different concentrations (5%, 10%, and 20%) duku stem bark extracts gel. Oral ulcers were induced on the lower lip mucosa of rats. Extract gels were applied three times daily for 14 days. Diameter of ulcer was measured on day 0, 3, 5, 7, 9, 11, 13, and 14. Kruskal Wallis and Pairwise Comparison test were used to analyze the data. Results: At day 13th, the 20% duku stem bark extract gel had significant lower ulcer diameters compared to another group (p <0,05). Conclusion: Duku (Lansium domesticum) stem bark extract gels could accelerate oral ulcer healing and could be used as an alternative natural topical drug for oral ulcer.